Speech-Swallow Dissociation of Velopharyngeal Incompetence with Pseudobulbar Palsy: Evaluation by High-Resolution Manometry - Miyagawa, Shinji; Yaguchi, Hiroshi; Kunieda, Kenjiro; Ohno, Tomohisa; Fujishima, Ichiro (Dysphagia, 2024)
Patients with pseudobulbar palsy often present with velopharyngeal incompetence. Velopharyngeal incompetence is usually observed during expiratory activities such as speech and/or blowing during laryngoscopy. These patients typically exhibit good velopharyngeal closure during swallowing, which is dissociated from expiratory activities. We named this phenomenon “speech-swallow dissociation” (SSD). SSD on endoscopic findings can help in diagnosing the underlying disease causing dysphagia. This endoscopic finding is qualitative, and the quantitative characteristics of SSD are still unclear. Accordingly, the current study aimed to quantitatively evaluate SSD in patients with pseudobulbar palsy. We evaluated velopharyngeal pressure during swallowing and expiratory activity in 10 healthy subjects and 10 patients with pseudobulbar palsy using high-resolution manometry, and compared the results between the two groups. No significant differences in maximal velopharyngeal contraction pressure (V-Pmax) were observed during dry swallowing between the pseudobulbar palsy group and healthy subjects (190.5 mmHg vs. 173.6 mmHg; P = 0.583). V-Pmax during speech was significantly decreased in the pseudobulbar palsy group (85.4 mmHg vs. 34.5 mmHg; P < 0.001). The degree of dissociation of speech to swallowing in V-Pmax, when compared across groups, exhibited a larger difference in the pseudobulbar palsy group, at 52% versus 80% (P = 0.001). Velopharyngeal pressure during blowing was similar to that during speech. Velopharyngeal closure in patients with pseudobulbar palsy exhibited weaker pressure during speech and blowing compared with swallowing, quantitatively confirming the presence of SSD. Pseudobulbar palsy often presents with SSD, and this finding may be helpful in differentiating the etiology of dysphagia.